PENERAPAN TEKNOLOGI BIODIGESTER SKALA RUMAH TANGGA SEBAGAI SARANA PENDUKUNG PRODUKSI SUSU KAMBING DI KUNCEN FARM MIJEN - Roihatin, Anis; Aulia, Nur Fatowil; Mulyono, Mulyono; Sahid, Sahid; Hendrawati, Dwiana; Prasetyo, Totok; Supriyo, Supriyo; Safaruddin, Yanuar Mahfudz (Politeknik Negeri Semarang, 2024)
Biogas is an environmentally friendly alternative energy source that is widely developed in society. Livestock waste is a source of biogas that is easy to obtain and the installation of digestion is easy, making biogas used by the community as an alternative to LPG. Kuncen Farm is a livestock farmer group that has a business cultivating dairy goats, fattening goats (Jawarandu Goats) and breeding Etawa goats. So far, goat manure waste is still managed conventionally, where only organic fertilizer is used for community agricultural needs and only makes up 30-50% of the total manure waste. Goat waste that is not used ends up being simply collected, producing an unpleasant odor and disturbing the environment. Based on the problems faced by Kuncen Farm and the potential of goat manure waste as a source of biogas, the application of biodigester technology on a household scale is a solution to goat manure waste as well as being a supporting facility for goat milk production at Kuncen Farm. This biodigester technology is made from PE plastic and utilizes used items around the house that can be used, such as used bottles, used stoves, motorbike tire rubber, etc. The main product in the form of biogas is used as fuel in gas stoves for goat's milk production and the by-product can be used as liquid fertilizer or organic compost which has economic value. This biogas stove can replace LPG fuel for cooking goat's milk. Furthermore, this biodigester technology can be installed on each group member.